The social evolution of international politics - Tang, Shiping (Oxford : Oxford University Press, 2013)
'The Social Evolution of International Politics' critically engages with all the key grand theories of international politics and provides interesting solutions to some of the'great debates' between those theories, from realism and neoliberalism, to the English School and constructivism.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 26, 2013).
Keywords: Political science -- Philosophy -- History